Effect of chilli varieties and storage conditions on quality attributes of honey chilli sauce: A preservation study. Issue 9 (26th July 2021) - Kaur, Manpreet; Aggarwal, Poonam; Kumar, Vikas
Abstract: The honey chilli sauce was standardized using green and red CH‐27 and Punjab sindhuri chilli varieties. The samples were stored at ambient (25 ± 2℃) as well as refrigeration (4 ± 2℃) temperature and analyzed for up to 8 months with 2 months interval. Honey chilli sauce with CH‐27 red was found to be significantly ( p  ≤ .05) highest in total phenolic components, beta carotene, lycopene and antioxidant activities while total solids, ash content and ascorbic acid content were highly retained in samples containing Punjab sindhuri red chilli variety. All the samples were acceptable even after 8 months of storage based on their sensory scores with intact nutrients. Novelty impact statement: Honey chilli sauce containing Punjab sindhuri red chilli scored the highest sensory scores due to its bright red color. Honey chilli sauce may add spice and flavor to cuisine and can be used as a wonderful dip aside from a dish. Value addition of chilli with honey can add flavor as well as health‐promoting properties of both to the food.